Dr, I Fractured My Prosthetic Knee - LIK HAN, ONG; Sabaruddin, A.; Jaffar, MSA; Bong, Chih How; Tan, KT; Reuben, P.R; Teh, HL; Kamaruddin, F. (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2022)
Pertiprosthetic fractures after total knee arthroplasty are challenging to treat. Tibial side are less commonly affected with only few studies and cases reported. We would like to present our patient that presented to us 5 years postoperative in whom revision rotating platform knee surgery was performed.